THE EFFECT OF PRODUCTION COSTS, PRODUCTION CAPACITY AND PRICES ON THE INCOME OF MELINJO CHIPS CRAFTSMEN IN PIDIE REGENCY - Fika Ayu Fina; Agustinawati (RADJA PUBLIKA, 2025)
This research aims to determine the effect of production costs, production capacity and prices on the income of melinjo chips craftsmen in Pidie Regency. The sample in this study amounted to 100 respondents melinjo chips craftsmen. The data were analyzed using multiple linear regression and the results show that production costs (X1) and prices (X3) have a positive and significant effect on the income of melinjo chips craftsmen in Pidie Regency, while production capacity (X2) has a negative and significant effect on the income of melinjo chips craftsmen in Pidie Regency. Thus, this research contributes to the development of the income of melinjo chips craftsmen. The implication of this research is the need for craftsmen to control production costs effectively and set competitive selling prices so that income can increase optimally.